(untitled) (Research, Society and Development, 2021)
Leishmaniasis groups some neglected diseases caused by intracellular protozoa Leishmania. Its main clinical forms are the tegumentary (LT) and Visceral (LV). Currently, the therapy against leishmaniasis is based on the use of five drugs: the pentavalent antimonials, amphotericin B and its liposomal formulation, miltefosine, paromomycin and pentamidine. These compounds present limitations that difficult patient’s adherence to treatment, such as high toxicity and the need for prolonged parenteral administration, in addition to the selection of resistant strains. Thus, employing the literature narrative review, we brought a panorama of the current leishmaniasis treatment, its elucidated action mechanisms, attributed toxicity, adverse effects and administration routes. Aiming to point this, the more updated data available in the literature were brought to facilitate access information on therapeutic options, in addition to new therapeutic alternatives and vaccine perspectives against this neglected disease.